2015
DOI: 10.2319/022515-118.1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of photobiomodulation with a matrix metalloproteinase inhibitor on the rate of relapse in rats

Abstract: Objective: To investigate combined effect of photobiomodulation with a matrix metalloproteinase (MMP) inhibitor on the relapse rate in relation to MMP expression in rats. Materials and Methods: Fifty-two rats were divided into four groups according to the treatment modality: control group, irradiation group, doxycycline group, and irradiation with doxycycline group. During a relapse period of 5 days after orthodontic movement, maxillary central incisors were treated by low-level laser therapy (LLLT) as a photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…The search identified a total of 2354 studies, of which 1633 studies were screened for titles and abstracts after the removal of duplicates. From the remaining 10 records that were assessed for eligibility, 3 studies were excluded because one included a period of retention before experimental relapse, 18 1 involved animals with pathological conditions, 19 and the full-text record of 1 study could not be retrieved. 20 Finally, seven studies were included in the qualitative synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
“…The search identified a total of 2354 studies, of which 1633 studies were screened for titles and abstracts after the removal of duplicates. From the remaining 10 records that were assessed for eligibility, 3 studies were excluded because one included a period of retention before experimental relapse, 18 1 involved animals with pathological conditions, 19 and the full-text record of 1 study could not be retrieved. 20 Finally, seven studies were included in the qualitative synthesis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Finally, this systematic review included three clinical trials [48][49][50] and ve animal studies [51][52][53][54][55]. Cohen's kappa coe cient values were 0.82 and 0.78 for the above two selection rounds, indicating a substantial agreement between the two reviewers.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Only tooth relapse and dental health in terms of root resorption were investigated out of all post-OTM outcomes, and no studies reported any impacts of LLLT on patients' subjective perceptions. For orthodontic relapse, two of the studies were CCTs [48,49] and the others were animal experiments [51][52][53]. These studies covered two types of tooth movement, rotational and transitional relapse.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations